Understanding child neglect in a gender context: a study performed in a Brazilian city - Emiko Yoshikawa Egry; Maíra Rosa Apostólico; Leda Maria Albuquerque; Rafaela Gessner; Rosa Maria Godoy Serpa da Fonseca (SciELO, 2015)
OBJECTIVETo describe the phenomenon of child neglect and understand it in a gender context.METHODRetrospective, quantitative, and exploratory study that analyzed reports of violence by a child and adolescent protection network in a Brazilian city. The theoretical and methodological basis applied was TIPESC (Theory of Nursing Praxical Intervention in Collective Health), with a gender emphasis.RESULTSNeglect of children under the age of ten represents more than half the reports received over all the years studied; more boys than girls suffered neglect and 41.4% of the reports of neglect involved children under than age of three; women were identified as being solely responsible in 67.9%, and as accessories in 17.3% of the incidents reported.CONCLUSIONChild neglect is a complex matter, the gender subordinate status inflicted on these children and their mothers who are responsible for their care underscore the social vulnerability of this group.